Nazwy kolorów w leksyce odzieżowej (na materiale Słownika ubiorów Ireny Turnau) - Borejszo, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The Dictionary of Clothing by Irena Turnau records 113 lexemes defining the colours of clothes and fabrics used in the Polish language from the 14th century until the beginning of the 19th century. The material collected by the author of the Dictionary originates from the sources that are seldom taken into account by lexicographers, that is from inventories, last wills, bills, the data recorded by guilds and merchandise official prices, and because of this a large group of words was not documented in the dictionaries of historical Polish and monographs devoted to the names of colours (in the index placed at the end of the article, such words have been highlighted with bold type). In the analysed material, a quite numerous group of loan words (mainly from French and Italian) is represented, used in Polish only periodically, but also the vernacular formations, most often found with the suffix -owy, derived from the word-forming bases being the names of flora, fauna and cookery, precious and semiprecious stones, minerals, metals, atmospheric phenomena etc. The names of various shades of red colour, then yellow, blue and green dominate among the lexical items describing the colours of clothes and fabrics. The remaining palette of colours is represented by fewer examples. We can include here such names of colours as: grey-brown, brown, violet and white. The descriptions of the colours of clothes and fabrics contained in the Dictionary of Clothes by Irena Turnau, do not fully represent a whole richness of lexicon of the studied semantic field. It is also difficult to answer unambiguously the question about the reasons which decided about this specific selection of material, because, next to the names which were not documented previously, there appears here also the generally known vocabulary which has been in use in the Polish language until today. Also, the author does not separate the lexicon used all over Poland from dialectal names.